Influence of gate insulator and AlGaN barrier layer on MISHEMT conduction mechanisms - Canales, Bruno G.; Martino, Joao A.; Agopian, Paula G. D. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2023)
The drain current in the Metal-Insulator-Semiconductor High Electron Mobility Transistor (MISHEMT) is studied as a function of AlGaN barrier layer thickness, Al molar fraction, and also the gate insulator thickness, focusing on the different MISHEMT conduction mechanisms. The device has a Si3N4/AlGAN/AlN/GaN heterostructure with 2 channels in the barrier layer - AlGaN (one field effect channel and one 2DEG) and 1 channel in the buffer layer - GaN (2DEG). It is observed that only the 2DEG channels activation voltages are affected by the barrier layer thickness and Al molar fraction, while the field effect conduction does not move away from the gate electrode. However all the channels are affected by altering the gate insulator thickness due to the transconductance changes.
Keywords: aluminum molar fraction; barrier layer thickness; gate insulator thickness; III-Nitride materials; MISHEMT